A novel portable device for crawling waves sonoelastography: Experimental study - Ancajima P.A. (2020)
Crawling Waves Sonoelastography (CWS) is an elastography technique based on an interference pattern produced by the application of two external vibration sources. In this study, a 3D printed holder was designed to overcome the compatibility limitations of normal excitation modules for different ultrasound systems, previously developed in the literature. This holder was assembled with a transducer and two voice coil actuators, and its performance was tested in homogeneous and inclusion tissue-mimicking phantom. A phase derivative estimator was used to reconstruct the shear wave speed (SWS) map. The coefficient of variation (CV), bias and contrast-to-noise ratio (CNR) were used as quantitative metrics for comparison. These metrics have shown a comparable SWS estimation in the background (SWSb) of the homogeneous phantom with previous studies (e.g. SWSb = 3.58± 0.42 m/s). In the same way, the SWS of the inclusion (SWSi) was distinguished from the background with an accurate SWS value (e.g. SWSi = 5.64 ±0.42 m/s and SWSb = 3.70 ±0.16 m/s). The results suggest that the portable device is capable of achieving a good performance according to their values of bias, CV and CNR. The extension of this work is oriented to ex vivo and in vivo experiments. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.